Workplace incivility and organizational citizenship behaviour: Moderated mediation model of work engagement and organizational identity - KARATAŞ GÜMÜŞTAŞ, NİLGÜN (My University, 2022)
Drawing on the tenets of conservation of resources theory and social identity theory, this study examined the influence of workplace incivility on organizational citizenship behaviour (OCB) through the mediating effect of work engagement. Simultaneously, the moderator effect of organizational identity on the relationship between workplace incivility and work engagement is analyzed. Using the data collected from 484 full time employees from hi-tech, banking and manufacturing industries, it is found that work engagement fully mediates the relationship between workplace incivility and OCB. Furthermore, it is found that the adverse impact of workplace incivility is higher for employees with greater organizational identification, implying that experiencing workplace incivility can be more devastating for employees who see their organization as an integral part of their identity. This study contributes to the literature by jointly testing the mediating role of work engagement and moderator role of organizational identity to understand the relationship between workplace incivility and OCB. Drawing on the findings, both theoretical and practical implications are discussed.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Social Sciences and Humanities; Psychology; Temel Bilimler (SCI); Natural Sciences (SCI); PSYCHOLOGY; Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; General Psychology; Social Sciences & Humanities; Organizational citizenship behaviour; Organizational identity; Work engagement; Workplace incivility